Management of Atypical Cranial Meningiomas, Part 2: Predictors of Progression and the Role of Adjuvant Radiation After Subtotal Resection. Issue 4 (12th June 2014) - Sun, Sam Q.; Cai, Chunyu; Murphy, Rory K.J.; DeWees, Todd; Dacey, Ralph G.; Grubb, Robert L.; Rich, Keith M.; Zipfel, Gregory J.; Dowling, Joshua L.; Leuthardt, Eric C.; Leonard, Jeffrey R.; Evans, John; et al.
Abstract: BACKGROUND: The efficacies of adjuvant stereotactic radiosurgery (SRS) and external beam radiation therapy (EBRT) for atypical meningiomas (AMs) after subtotal resection (STR) remain unclear. OBJECTIVE: To analyze the clinical, histopathological, and radiographic features associated with progression in AM patients after STR. METHODS: Fifty-nine primary AMs after STR were examined for predictors of progression, including the impact of SRS and EBRT, in a retrospective cohort study. RESULTS: Twenty-seven patients (46%) progressed after STR (median, 30 months). On univariate analysis, spontaneous necrosis positively (hazard ratio = 5.2; P = .006) and adjuvant radiation negatively (hazard ratio = 0.3; P = .009) correlated with progression; on multivariate analysis, only adjuvant radiation remained independently significant (hazard ratio = 0.3; P = .006). SRS and EBRT were associated with greater local control (LC; P = .02) and progression-free survival ( P = .007). The 2-, 5-, and 10-year actuarial LC rates after STR vs STR/EBRT were 60%, 34%, and 34% vs 96%, 65%, and 45%. The 2-, 5-, and 10-year actuarial progression-free survival rates after STR vs STR/EBRT were 60%, 30%, and 26% vs 96%, 65%, and 45%. Compared with STR alone, adjuvant radiation therapy significantly improved LC in AMs that lack spontaneous necrosis ( P = .003) but did not improve LC in AMs with spontaneous necrosis ( P = .6). CONCLUSION: Adjuvant SRS or EBRT improved LC of AMs after STR but only for tumors without spontaneous necrosis. Spontaneous necrosis may aid in decisions to administer adjuvant SRS or EBRT after STR of AMs.